2019
DOI: 10.1158/1055-9965.epi-18-0917
|View full text |Cite
|
Sign up to set email alerts
|

Disparities and Trends in Genetic Testing and Erlotinib Treatment among Metastatic Non–Small Cell Lung Cancer Patients

Abstract: Background: Despite reports of socioeconomic disparities in rates of genetic testing and targeted therapy treatment for metastatic non-small cell lung cancer (NSCLC), little is known about whether such disparities are changing over time.Methods: We performed a retrospective analysis to identify disparities and trends in genetic testing and treatment with erlotinib. Using the Surveillance, Epidemiology, and End Results (SEER)-Medicare database, we identified 9,900 patients with stage IV NSCLC diagnosed in 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…1) and were included in the review. Eight studies reported utilization data for predictive biomarker tests [21][22][23][24][25][26][27][28], thirty-seven studies (41 papers) reported utilization data for biological and precision therapies , and 3 studies reported both [66][67][68]. Ten papers (Additional file 1: Table S1) had no denominator populations or only reported an average measure of socio-economic status (e.g., mean household income), and were excluded from inclusion in the meta-analysis and are not discussed further [69][70][71][72][73][74][75][76][77][78].…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1) and were included in the review. Eight studies reported utilization data for predictive biomarker tests [21][22][23][24][25][26][27][28], thirty-seven studies (41 papers) reported utilization data for biological and precision therapies , and 3 studies reported both [66][67][68]. Ten papers (Additional file 1: Table S1) had no denominator populations or only reported an average measure of socio-economic status (e.g., mean household income), and were excluded from inclusion in the meta-analysis and are not discussed further [69][70][71][72][73][74][75][76][77][78].…”
Section: Search Resultsmentioning
confidence: 99%
“…The 48 included studies covered 7 cancers, 5 predictive biomarker tests, and 11 biological and precision therapy classifications, of which bevacizumab (12 studies) [ 41 – 45 , 54 56 , 58 , 59 , 64 , 65 ] and trastuzumab (11 studies) [ 29 39 ] were most common. Most studies were in the USA ( n = 42) [ 21 , 22 , 25 – 35 , 40 68 ], and a majority analyzed SEER registry data ( n = 27) [ 21 , 22 , 25 , 29 33 , 41 , 42 , 45 , 47 , 49 , 50 , 54 59 , 61 64 , 66 68 ] (Additional file 1 : Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations